Exploring teacher feedback and student participation in an Indonesian University EFL classroom: A qualitative study - Hensem Alambana; Septian Ulul Albab; Julia Crist Ei Riyanti; Awaludin Khasan; Abdullah Mukhlis; Muhammad Rizqi; Dewi Puspitasari (Privietlab, 2026)
Teacher feedback plays a central role in English as a Foreign Language (EFL) classrooms because it supports students' language development and shapes the quality of classroom interaction. Although previous studies have extensively examined teacher feedback and classroom interaction, these areas have often been investigated separately, resulting in a limited understanding of how different forms of teacher feedback function within naturally occurring classroom discourse. This study investigates the connection between teacher feedback and student participation in an EFL class at an Indonesian university through qualitative discourse analysis utilizing the Initiation-Response-Feedback (IRF) model. Data for this research were gathered from four non-participant classroom observations. The audio recordings were transcribed verbatim and analyzed to examine how teacher feedback functioned within interactional sequences and influenced subsequent student participation. The findings identified three types of teacher feedback: corrective, evaluative, and interactional. Corrective feedback primarily functions as a repair, promoting immediate student uptake and linguistic accuracy. Evaluative feedback acknowledged students' responses but generally closed the interactional sequence. In contrast, interactional feedback functioned as a continuation move by encouraging follow-up responses, extended explanations, and additional interactional turns, thereby fostering sustained verbal participation. These findings suggest that teacher feedback should not only be understood as a pedagogical strategy for improving linguistic accuracy but also as an interactional resource that shapes the development of classroom discourse. This study contributes to EFL classroom discourse research by demonstrating how different feedback practices function within IRF sequences and offers practical implications for lecturers seeking to foster more interactive and participatory learning environments in their classrooms.